OPTIMASI KANDUNGAN NUTRISI PAKAN IKAN BUATAN DENGAN MENGGUNAKAN MULTI OBJECTIVE (GOAL) PROGRAMMING MODEL - Vera Devani (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2015)
Freshwater fish farming has become an inseparable agribusiness activities with fish feed industry. Fish food must contain nutrients in accordance with the needs of fish. There are three nutrients in fish feed are protein, carbohydrates, and fats. To determine the combination of artificial fish feed raw materials that contain all three nutrients required an appropriate method. By using the Multi-Objective (Goal) Programming can be known nutrient needs of each artificial fish feed raw materials, the content of nutrients in feed raw material and operating costs of artificial fish feed manufacturing artificial fish. Based on the results obtained by using the software LINGO nutrients in 100 kg of fish feed raw materials made of 20 kg of protein, carbohydrates 30 kg, and 5.2 kg of fat with fish feed manufacturing cost savings made by Rp 35139.76 (20%).